Pengaruh Literasi Keuangan Dan Perilaku Keuangan Terhadap Keputusan Investasi Pada Galeri Invesatasi Universitas Ngurah Rai - Made Ayu Desy Geriadi; Putu Surya Septiani (Jurnal Ilmiah Satyagraha, 2025)
This research aims to examine the influence of financial literacy andfinancial behavior on stock investment decisions. This research was conducted atthe Investment Gallery of Ngurah Rai University. This research uses quantitativedata using primary and secondary data sources. The data collection method uses aquestionnaire which is measured using a Likert scale. The population in this studywere students who were registered as investors at the Ngurah Rai UniversityInvestment Gallery from 2019 to 2023, totaling 703 people. The sampling techniqueused purposive sampling technique, so the total sample was 56 people. Dataprocessing uses the SPSS version 25 for Windows program. The researchinstrument uses validity and reliability tests. Data analysis uses the classicassumption test, multiple linear regression analysis, determination analysis, F testand t test. The research results show that (1) financial literacy and financialbehavior have a positive and significant effect simultaneously on investmentdecisions, (2) financial literacy has a partial positive and significant effect on investment decisions and (3) financial behavior has a partial positive and significant effect. significant influence on decisions. investment.